Association between education about organ transplantation aimed at medical students and the acquisition of the organ donor card. A cross-sectional study. (2014)
Background. The transplantation group of the National University of Colombia considers that education about transplants is important to raise the donation rate in this country.Objective. To find a statistical association between education about transplantation aimed at medical students and the number of students and their families bearing the organ donor card.Materials and methods. Cross-sectional analytical study. Two surveys were designed and sent to two different student populations. The first group had taken the course “Human Organ and Tissue Transplantation”, and the second group was composed of students from the fifth semester of medical education. The statistical test used was difference of proportions, sample size of 50 people, statistical power of 80%, difference in proportions 20%, alpha 0.05, p 0.05.Results. The surveys were answered by 29 students from first group and 74 students from second group. First question: “Do you carry the organ donor card?”, p-value of 0.03 found. Second question: “Do your family members carry the organ donor card?”, p-value of 0.732 found. Affirmative answer to the first question, p=0.10 and answer to second question, p=0.0005.Conclusion. An association was found between education about transplantation focused on medical students and bearing the organ donor card and communicating their wishes to their families. Likewise, an association between education and a positive attitude toward donation was found in the families of students that participated on the course “Human Organ and Tissue Transplantation”.